2021
DOI: 10.3390/pathogens10040433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil-Borne Inoculum of Plasmodiophora brassicae Measured by qPCR on Disease Severity of Clubroot-Resistant Cultivars of Winter Oilseed Rape (Brassica napus L.)

Abstract: Use of resistant cultivars is considered the most effective tool in managing clubroot. Three clubroot-resistant commercial winter oilseed rape (OSR) cultivars and a susceptible ‘Cultivar mix’ were evaluated for disease severity index (DSI) and yield performance in field soils, selected for varying abundance of natural inoculum of Plasmodiophora brassicae. Seven field trials were carried out during 2017–2019 in winter OSR crops, and comparative bioassays were performed in a growth chamber. Substantial variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…(4) Breeding for disease-resistance cultivars: Field management can reduce disease incidence to some extent, but it requires a lot of labor and at the same time does not fundamentally solve the problem. Indeed, researchers have tried to quantify the abundance of clubroot pathogens using the qRT-PCR method, although in most cases the pathogen is present in a mixed population [50]. Comparative bioassays performed in growth chambers showed that resistance was under selection pressure, and the use of clubroot-resistant cultivars is recommended when P. brassicae DNA exceeds 1300 genes copies per gram soil [50].…”
Section: Control Measures Of Clubroot Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…(4) Breeding for disease-resistance cultivars: Field management can reduce disease incidence to some extent, but it requires a lot of labor and at the same time does not fundamentally solve the problem. Indeed, researchers have tried to quantify the abundance of clubroot pathogens using the qRT-PCR method, although in most cases the pathogen is present in a mixed population [50]. Comparative bioassays performed in growth chambers showed that resistance was under selection pressure, and the use of clubroot-resistant cultivars is recommended when P. brassicae DNA exceeds 1300 genes copies per gram soil [50].…”
Section: Control Measures Of Clubroot Diseasementioning
confidence: 99%
“…Indeed, researchers have tried to quantify the abundance of clubroot pathogens using the qRT-PCR method, although in most cases the pathogen is present in a mixed population [50]. Comparative bioassays performed in growth chambers showed that resistance was under selection pressure, and the use of clubroot-resistant cultivars is recommended when P. brassicae DNA exceeds 1300 genes copies per gram soil [50]. Chemical control can be efficient but is costly and causes environmental pollution.…”
Section: Control Measures Of Clubroot Diseasementioning
confidence: 99%